Correlation between slump, VeBe and compaction factor of concrete containing shredded PET bottles, manufactured sand (M-sand) and river sand as fine aggregate - Nadimalla, Altamashuddinkhan; Masjuki, Siti Aliyyah; Saad, Siti Asmahani; Ali, Maisarah; Md Husain, Nadiah; Wan Azahar, Wan Nur Aifa; Kasim, Norhidayu (IOP Publishing Ltd, 2021)
This paper investigates the effects of the properties of fresh concrete incorporating shredded Polyethylene Terephthalate (PET) bottles and Manufactured Sand (M-sand) together as fine aggregates replacement in concrete mixtures. The investigation to determine the correlation of the fresh properties of concrete were mainly experimental based and the experiments involved were Slump Test, VeBe Test and Compaction Factor Test. There were two different concrete batches were prepared, in which the first batch was partially replaced by Msand and the second batch was partially replaced by M-sand and shredded PET bottles as fine aggregate replacements. The proportion of M-sand content and M-sand with shredded PET bottles were 25%, 50%, 75% and 100% (for M-sand) and 1.5% proportion of shredded PET bottles respectively. The mix design was prepared in accordance to the Department of Environment (DOE) method and utilizes M30 as the Class of Concrete. A novel empirical relationship between slump, VeBe, and compaction factor for the shredded PET bottles and MSand based M30 concrete was proposed. The outcomes of this research has proven beneficial to the construction industries as the utilisation of waste and recycled materials has the potential for sustainable construction.